Two Effects of Cytokinin on the Auxin Requirement of Tobacco Callus Cultures - Einset, John W. (1977)
Cytokinin affects the requirement for auxin of a strain of tobacco callus (Nicotiana tabacum) which is cytokinin-autotrophic when grown on Murashige and Skoog medium with 11.4 μm of indole-3-acetic acid but requires cytokinin 6-(3-methyl-2-butenylamino)purine (i(6) Ade) when grown on the same medium with <3 μm indole-3-acetic acid. As the exogenous concentration of cytokinin (i(6) Ade) is increased, the concentration of indole-3-acetic acid required for growth is decreased. A second effect of cytokinin, observed sporadically in cultures with 2.5 μm or 5 μm i(6) Ade, is the transformation of some of the callus pieces to auxin-autotrophic growth. Strains, both callus-forming and bud-forming tissues, that arise in this manner are not permanently altered in their auxin requirement because subcultures on medium without cytokinin still require exogenous auxin.